Impact of the sewage discharge from hot springs to water sources - Romero Rojas, Jairo Alberto; Sanchez Londoño, Yuly Andrea; Quiñones-Bolaños, Edgar; Rodriguez Cheu, Luis Eduardo; González Leal, Rocío; Mehrvar, Mehrab; McCarthy, Lynda; Reuss, Alexander (Asociación Colombiana de Facultades de Ingeniería - ACOFI, 2021)
Hot springs have traditionally been a tourist attraction in many parts of the world, such as Japan, Canada, Taiwan among others. During the peak tourist season, it is usually discharged into streams without treatment, which can affect the quality of the receiving water, causing negative impacts to the aquatic ecosystems. Downstream ecological impacts of several major spa recreational sites in different parts of the world have been studied, and it has been found that wastewater discharges of hot springs have adverse ecological effects. The mineral composition in hot springs, derived mainly from groundwater, is usually greater than that of stream water. Studies carried out with models such as QUAL2K (or Q2K), the modernized version of the QUAL2E (or Q2E), simulate the effect of the hot spring discharges on surface water sources, mainly negative in nature. Despite the negative consequences of the impacts on ecosystems derived from hot springs’ wastewater, it is interesting to note that there are regulations for wastewater discharges – including backwash water from swimming pools – into rivers and sewers (e.g., Germany and Canada), but not specifically for hot springs discharge. Nonetheless, this evidence indicates a necessity for the authorities to increase the control of the use of hot springs and the discharge of their untreated waters. In Colombia, Resolution 631 of 2015 regulates the discharge of wastewater into rivers and sewers. Yet, it does not consider parameters for the discharge of hot springs. However, the authors deem it necessary to advance in the investigation on the contamination of the wastewaters coming from hot springs, and think about a sustainable tourism of hot springs.

Las aguas termales han sido tradicionalmente una atracción turística en muchas partes del mundo, como Japón, Canadá, Taiwán, entre otros. Durante la temporada alta de turismo, se suele descargar a arroyos sin tratamiento, lo que puede afectar la calidad del agua receptora, provocando impactos negativos en los ecosistemas acuáticos. Se han estudiado los impactos ecológicos aguas abajo de varios sitios recreativos de spa importantes en diferentes partes del mundo, y se ha encontrado que las descargas de aguas residuales de las aguas termales tienen efectos ecológicos adversos. La composición mineral de las aguas termales, derivada principalmente de las aguas subterráneas, suele ser mayor que la del agua de los arroyos. Estudios realizados con modelos como QUAL2K (o Q2K), la versión modernizada del QUAL2E (o Q2E), simulan el efecto de las descargas de aguas termales en fuentes de agua superficial, principalmente de naturaleza negativa. A pesar de las consecuencias negativas de los impactos en los ecosistemas derivados de las aguas residuales de las fuentes termales, es interesante notar que existen regulaciones para las descargas de aguas residuales, incluidas las aguas de retrolavado de piscinas, en ríos y alcantarillas (por ejemplo, Alemania y Canadá), pero no específicamente para la descarga de aguas termales. Sin embargo, esta evidencia indica la necesidad de que las autoridades aumenten el control del uso de las aguas termales y la descarga de sus aguas no tratadas. En Colombia, la Resolución 631 de 2015 regula la descarga de aguas residuales en ríos y alcantarillados. Sin embargo, no considera parámetros para la descarga de aguas termales. Sin embargo, los autores consideran necesario avanzar en la investigación sobre la contaminación de las aguas residuales provenientes de aguas termales, y pensar en un turismo sustentable de aguas termales.
Keywords: Discharge; Hot springs; Impact; Untreated; Alta; Aguas termales; Impacto; Sin tratar